BIOPOLITICS AND HOMO SACER IN A TORTURE CENTER IN CHILE * - Hugo Rojas Corral (Revista Direito GV)
This article explains how the concepts of Biopolitics and homo sacer contribute to the understanding of what happened in the Villa Grimaldi concentration camp and torture center during the dictatorship of General Augusto Pinochet, in Chile. Prisoners were humiliated and tortured, losing their condition as subjects of law. The reification process of the prisoners by sadist guards and agents was added to the impossibility of the victims to legally defend themselves in front of tribunals. The archaic Roman law figure of homo saceris perfectly applicable to explain the situation of the persons kept in clandestine concentration camps as Villa Grimaldi. The notion of superstes tormentorum (survivor of tortures) is also presented here for further discussion in order to refer to the complex and often painful process in which the ‘victims-survivors-witnesses’ of the horror of Villa Grimaldi and other similar spaces try to reinsert in society.